Assessing the Impact of Financial Performance Metrics on Profit Growth: Evidence from LQ45 Companies Listed on the Indonesia Stock Exchange - Priyono, Achmad Agus; Saraswati, Ety; Widarko, Agus (Fokus Bisnis Media Pengkajian Manajemen dan Akuntansi, 2024)
This research investigates how financial performance metrics influence profit growth amongst firms listed on the Indonesia Stock Exchange's (IDX) LQ45 Index from 2016 to 2023. Employing a quantitative methodology and utilizing secondary data derived from financial reports, this investigation assesses the influence of five crucial financial ratios: current ratio (CR), debt-to-equity ratio (DER), return on assets (ROA), gross profit margin (GPM), and net profit margin (NPM). Panel data regression techniques assess the relationship between these indicators and profit growth. The results show that ROA positively and significantly affects profit growth, whereas CR negatively impacts profit growth. By contrast, DER, GPM, and NPM did not have statistically significant effects. These results underscore the significance of effective resource utilization and cash flow management in boosting profitability. The research offers crucial insights for business decision-makers, especially in refining financial approaches within Indonesia's regulatory framework and market conditions.